Multicenter retrospective evaluation of transmural migration of subcutaneous ureteral bypass devices within the digestive tract in cats. (17th August 2022) - Véran, Emilie; Vachon, Catherine; Byron, Julie; Howard, James; Berent, Allyson; Weisse, Chick; Javard, Romain; Spencer, Ashley; Gradilla, Sarah; Palm, Carrie; Culp, William; Cléroux, Andréanne; et al.
Abstract: Background: Placement of a subcutaneous ureteral bypass (SUB) device is an effective method to relieve all causes of ureteral obstruction in cats. Complications involving migration within the gastrointestinal tract have been seldomly described. Objectives: To characterize transmural migration of SUB devices within the digestive tract in cats. Animals: Eleven migrated SUB catheters identified in 8 cats between 2017 and 2021. Methods: Retrospective review of medical records of cats with a SUB device in which migration into the gastrointestinal tract was identified. Results: The median time from SUB device placement to implant migration was 928 days (201‐2298 days). Seven cats had obstruction of the SUB device and a positive urine culture at diagnosis. The migration was identified by ultrasound in 6/11, pre‐operative contrast radiography in 2/2, and only at time of surgery in 3 SUB devices. All cats underwent surgical correction. Four nephrostomy and 7 cystotomy catheters migrated. Migration occurred into the duodenum (3/11), jejunum (7/11), and colon (1/11). SUB devices were removed in 7 cats and replaced in 2 cats, with 1 cat diagnosed with 2 migration events. Gastrointestinal resection and anastomosis were performed in 7/8 cats and an enterotomy in 2 cats. Six cats survived to discharge. The median follow‐up time after migration diagnosis was 365 days (range, 0‐1114 days) and 2 cats are still alive. Conclusions and Clinical Importance: Although a rare complication, migration of SUB device should be considered in cats with SUB device obstruction and a positive urine culture.